2015
DOI: 10.1371/journal.pone.0139537
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Prey-Trap Hypothesis at Two Wildlife Conservancies in Kenya

Abstract: Protecting an endangered and highly poached species can conflict with providing an open and ecologically connected landscape for coexisting species. In Kenya, about half of the black rhino (Diceros bicornis) live in electrically fenced private conservancies. Purpose-built fence-gaps permit some landscape connectivity for elephant while restricting rhino from escaping. We monitored the usage patterns at these gaps by motion-triggered cameras and found high traffic volumes and predictable patterns of prey moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…We speculate that prey may dilute their predation risk through spatiotemporal clustering when using wildlife passages, either incidentally or adaptively. Our results are consistent with the few other studies that tested the prey-trap hypothesis in association with wildlife passages, suggesting such traps do not occur or are difficult to detect 19,24 . Despite our lack of support for it, we suggest that the prey-trap hypothesis merits additional study in other systems, areas, and taxa.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We speculate that prey may dilute their predation risk through spatiotemporal clustering when using wildlife passages, either incidentally or adaptively. Our results are consistent with the few other studies that tested the prey-trap hypothesis in association with wildlife passages, suggesting such traps do not occur or are difficult to detect 19,24 . Despite our lack of support for it, we suggest that the prey-trap hypothesis merits additional study in other systems, areas, and taxa.…”
Section: Discussionsupporting
confidence: 92%
“…Each of these circumstances could have increased the benefit or ease of prey tracking by predators by increasing detection rates or learning opportunities by predators [26][27][28][29] . A viable interpretation of our results is that low predator, relative to prey, abundance generally limits the likelihood of prey-traps at wildlife passages here and elsewhere 19,24 . For a prey-trap to occur, predators would have to detect (i.e., visually or olfactorily) and encounter prey inside wildlife passages with sufficient frequency to develop search images (sensu [57][58][59].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, fence-gaps create pinch-points in the landscape where wildlife migratory movement is artificially funneled and thus, this could create prey-traps ( Ford & Clevenger, 2010 ). Although, both prey and predator species use the fence-gaps, we have found that predators do not hunt near these fence-gaps, possibly because of the constant elephant traffic ( Dupuis-Desormeaux et al, 2015 ). One of these three fence-gaps, the western gap, connected two adjacent wildlife conservancies (from 2009 to 2015).…”
Section: Introductionmentioning
confidence: 92%
“…This spatial predictability of animal movement could potentially lead to predators exploiting the fence-gaps and eventually lead to an imbalance of the predator-prey dynamic. A recent study by Dupuis-Desormeaux et al (2015) found that fence gaps on the Lewa and neighbouring Borana conservancies did not act as prey-traps, but managers contemplating the use of fence-gaps should monitor the dynamics of predator-prey interactions near the fence gaps for the potential emergence of prey-traps.…”
Section: Risks Of the Development Of A Prey-trapmentioning
confidence: 99%